2021
DOI: 10.1080/09640568.2021.1971069
|View full text |Cite
|
Sign up to set email alerts
|

The paradox of planning the compact and green city: analyzing land-use change in Amsterdam and Brussels

Abstract: Strategies applied by urban policy makers in order to achieve sustainable city development may be in conflict with each other because it crosses many disciplines and policy areas. This research focusses on the dilemma between compact city and urban greenspace policies and their influence on actual land-use change in Amsterdam and Brussels. These cases are selected because of their similar urban growth yet diverse policy and governance contexts. We contend that comparing how urban policies try to address this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Urban densification has also been found incompatible with preserving urban green space. An analysis based in Brussels and Amsterdam showed that densification processes reduced the quantity of urban green spaces and negatively affected their connectivity and average size (Balikci, Giezen and Arundel 2021). The study attributed this to the inadequacy of existing green land use policies and their inability to offset the pressures resulting from densification.…”
Section: How Sustainable Are Compact Cities?mentioning
confidence: 94%
See 3 more Smart Citations
“…Urban densification has also been found incompatible with preserving urban green space. An analysis based in Brussels and Amsterdam showed that densification processes reduced the quantity of urban green spaces and negatively affected their connectivity and average size (Balikci, Giezen and Arundel 2021). The study attributed this to the inadequacy of existing green land use policies and their inability to offset the pressures resulting from densification.…”
Section: How Sustainable Are Compact Cities?mentioning
confidence: 94%
“…What emerges is a vision for a policy model comprised of a set of integrated strategies that are concerned with: urban growth containment; density optimization; functions, and social groups collocation; accessibility enhancement and multimodal mobility enablement; green structure preservation. The five core elements distilled herein are neither exhaustive nor limited, but they offer those interested in applying this model to new contexts an adaptable conceptual framework that directs their attention toward the links, mechanisms, policies, and strategies by which different combinations of elements can produce desirable and sustainable planning outcomes. Furthermore, this conceptual framework joins a trending perspective that considers the compact city holistically as an integrated system of design elements and principles, the synergy among which renders the concept more than a total sum of its parts (Bay 2017; Bhagwat and Devadas 2020; Bibri 2020 a ; Stevenson and Gleeson 2018).…”
Section: Compact City Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Song [79] analyzed the cultivated land use change in China from 1999 to 2007, and they suggested the development of multifunctional land management policies based on regional differences to promote the sound development of cultivated land protection. Balikci [80] found a disconnect between realistic trends in urban land use change and urban green space policies through an analysis of the urban green space policies and compact urban development policies of Amsterdam and Brussels.…”
Section: Response Planning and Policymentioning
confidence: 99%